The intellectual structure of sustainable business development studies - Kharchuk, Viktoriya; Oleksiv, Ihor; Shulyar, Roman; Shpak, Nestor (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This paper aims to examine the intellectual structure of sustainable business development studies and to gain an in-depth perspective on its future development. To achieve the research objectives, we applied methods of bibliometric analysis (WoS tools, co-citation analysis, co-word analysis, and bibliographic coupling) to the dataset extracted from the Web of Science. The main research domains of the researched field were distinguished based on the cluster interpretation. Specifically, both co-word analysis and bibliographic coupling demonstrated the overlap between the two research domains: "Sustainable Development and Entrepreneurship" and "Corporate Social Responsibility and Stakeholder Theory," while the "Sustainable Development: Theoretical Foundations of the Research" cluster obtained via bibliographic coupling partially converged with the "Sustainable Development and Entrepreneurship" cluster received from the co-word analysis. However, the clusters "Company Performance and Innovations" extracted from co-word analysis and "Competitive Analysis and Sustainable Development" obtained from bibliographic coupling did not coincide. Furthermore, we concluded that over the last 40 years, sustainable business development studies have gone through the process of structuring induced by global changes in business and the economy.